Legal Education Perspectives on Social Reactions and Sentencing Disparities in Mutilation Cases - Syalwah Az Zahra; Nailah Ikmal (Yayasan Cerdas Pedia Indonesia, 2025)
This research examines the critical intersection of judicial decision-making, social media influence, and legal education regarding premeditated mutilation cases in Indonesia. Utilizing a hybrid normative-legal and socio-legal methodology, the study analyzes sentencing disparities under Article 340 of the Criminal Code and Law Number 1 of 2023. Findings reveal that systemic inconsistencies arise from a widespread failure to evaluate perpetrator motives and an increasing susceptibility to